Graphene nanocomposites for real-time electrochemical sensing of nitric oxide in biological systems - Tabish, Tanveer A. (Appl Phys Rev, 2023)
Nitric oxide (NO) signaling plays many pivotal roles impacting almost every organ function in mammalian physiology, most notably in cardiovascular homeostasis, inflammation, and neurological regulation. Consequently, the ability to make real-time and continuous measurements of NO is a prerequisite research tool to understand fundamental biology in health and disease. Despite considerable success in the electrochemical sensing of NO, challenges remain to optimize rapid and highly sensitive detection, without interference from other species, in both cultured cells and in vivo. Achieving these goals depends on the choice of electrode material and the electrode surface modification, with graphene nanostructures recently reported to enhance the electrocatalytic detection of NO. Due to its single-atom thickness, high specific surface area, and highest electron mobility, graphene holds promise for electrochemical sensing of NO with unprecedented sensitivity and specificity even at sub-nanomolar concentrations. The non-covalent functionalization of graphene through supermolecular interactions, including π–π stacking and electrostatic interaction, facilitates the successful immobilization of other high electrolytic materials and heme biomolecules on graphene while maintaining the structural integrity and morphology of graphene sheets. Such nanocomposites have been optimized for the highly sensitive and specific detection of NO under physiologically relevant conditions. In this review, we examine the building blocks of these graphene-based electrochemical sensors, including the conjugation of different electrolytic materials and biomolecules on graphene, and sensing mechanisms, by reflecting on the recent developments in materials and engineering for real-time detection of NO in biological systems.